2021
DOI: 10.9734/ajmah/2021/v19i130295
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Knowledge and Practice of Handwashing among Healthcare Workers in a Tertiary Hospital in Ekiti, Southwestern Nigeria

Abstract: Background: The most common means of transmission of Healthcare-Associated Infections (HAIs) is the contaminated hand of Healthcare Workers (HCWs), proper handwashing by HCWs is the best method of halting this transmission, however, there is poor adherence to the practice of the simple handwashing procedure in many health facilities. Aims: To assess the knowledge and practice of proper handwashing, to identify the factors impeding adherence to its good practice among HCWs and to identify the handwashing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Similar to the present study, other studies[ 22 25 ] had reported positive influence of training on HH knowledge. The finding that a formal training in HH significantly increased knowledge of HH is most welcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the present study, other studies[ 22 25 ] had reported positive influence of training on HH knowledge. The finding that a formal training in HH significantly increased knowledge of HH is most welcome.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies, in contrast, reported association of HH knowledge with professional category[ 9 24 ] as well as with gender. [ 19 26 ] Both positive[ 25 ] and negative[ 18 ] relationships have been reported between long work experience and HH knowledge. In the present study, no statistically significant association was found between work experience and HH knowledge ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent hand washing has been documented as a potent measure for reducing the risk of MRSA carriage among HCWs since MRSA strains spread through contaminated hands [26]. While policy on handwashing is existent in our centre, previous study in the setting revealed generally poor handwashing knowledge in which only 31.1% of HCWs had good knowledge of handwashing and only 16.46% had previous training on handwashing, also, most (68.6%) respondents in that study still relied on 'stored' water (rather than tap/running water) for the purpose of handwashing while hand drying facility available to most respondents (86.28%) was the common towel (shared by all after handwashing) and no respondents ever used paper towel [27]. All these findings showed poor adherence to existing policies on handwashing in our setting.…”
Section: Discussionmentioning
confidence: 74%
“…This perception has some epidemiological foundation [ 44 , 45 ]. Similar experiences among young adults in Malawi [ 30 ], Tanzania [ 46 ], and South Africa [ 45 ] underscore the widespread lack of autonomy young women have when engaging in transactional sex even when they initiate such relationships [ 47 ]. In the context of widespread transactional sex, youth believe older men contribute to HIV transmission, creating the perceived dynamic of increased infection rates among both young women and young men due to such age-asymmetrical relationships [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social and sexual scripts can be inherited from parents and communities but they can also be mediated or transmitted by peers within one’s age cohort. These scripts often underlie the dynamics which give rise to different risk scenarios for young men compared to young women, as noted in studies on risk behaviour [ 4 , 30 ] and the societal expectations driving those differences. Crucially, social scripts are dynamic; when two or more actors are aware their scripts differ, as in intercultural exchanges, a new script can be negotiated or ‘co-written’ between two actors to smooth interactions and set common expectations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%